The Role and Challenges of Islamic Religious Education After the Covid 19 Pandemic - Hendrawati, Titi; Alberto, Seelaender; Manyullei, Syamsuar; Kurdi, Musyarrafah Sulaiman; Mustofa, Idam (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
As can be seen at this time, a pandemic emerged in 2019, which caused life to not run properly, even though the pandemic has passed, the shadows of the pandemic are still felt today, as well as in the field of education. In the end, the impact that occurs is the difficulty of students in understanding learning, because of their limitations in using media. The purpose of this study is to determine the role and challenges of Islamic religious education after the covid 19 pandemic. Researchers use quantitative methods using survey models and in-depth interviews. The survey used in this research is online-based using the WhatsApp and Google Form applications. This research results in the formation of Islamic religious values in students, where students can know the importance of learning Islamic religious education in everyday life. Researchers can conclude that the role and challenges faced by an educator after covid 19 are enormous. The limitations of this study, researchers are only able to instill religious values in students for everyday life. Researchers hope that further research will not only focus on religious education, but can instill other values.